Socialization Making Media Learning Interactive E-Module based Flippbook in Elementary School 4 Maiwa - Sam Hermansyah; Nasmilah Nasmilah; Abidin Pammu; Noer Jihad Saleh; Han Huazheng; Huang Congzhao (Pengabdian: Jurnal Abdimas, 2023)
The learning process will be more effective if it uses many learning resources, one of which is a module. For efficiency, modules can be packaged into a digital form called e-module based philipbook. From facet access And convenience in bring, e-module Can accessed And opened anywhere is at. On study This done socialization making media e-module based flipbook to elementary school teachers through stages planning, implementation, And taking questionnaire data follow-up after training. Results media implementation based E-Module learning Flipbooks teachers can develop Flipbook-based E-Module learning media so that the process teaching and learning between educators and students becomes more optimal and fun as well increase enthusiastic And Spirit in learning.